Role of Diffusion-Weighted MRI in the Detection of Early Active Sacroiliitis - Bozgeyik, Zulkif; Ozgocmen, Salih; Kocakoc, Ercan (Amer Roentgen Ray Soc, 2008)
OBJECTIVE. This study proposed to evaluate the value of diffusion-weighted MRI (DWI) to detect active inflammatory changes in the sacroiliac joints of patients with early axial spondyloarthritis (also spelled spondylarthritis). SUBJECTS AND METHODS. Forty-two patients with chronic low back pain underwent clinical and MRI evaluation for axial spondyloarthritis or early ankylosing spondylitis. STIR, contrast-enhanced T1-weighted, fat-saturated T2-weighted, and diffusion-weighted (b values: 100, 600, 1,000 s/mm(2)) images were obtained. The presence of subchondral bone marrow edema, subchondral fatty marrow infiltration, or contrast enhancement in the sacroiliac joints or adjacent enthesitis sites was considered a marker for active inflammatory changes. All MRI sequences were evaluated for the presence of acute inflammatory changes and inter- and intrarater reliability of the sequences. Mean apparent diffusion coefficient (ADC) values of diffusion-weighted images were calculated from normal and involved iliac and sacral bones of sacroiliac joints. RESULTS. ADC values measured from the lesions at b values of 1,000 and 600 s/mm(2) in patients with sacroiliitis (n = 13) were significantly higher than values measured from iliac and sacral bones in patients with low back pain of mechanical origin (n = 29). DWI showed sensitivity for detecting acute lesions in early sacroiliitis similar to that of TI-weighted gadolinium images (area under the curve, 0.843-0.971). Intra- and interrater reliability of DWI was acceptable. CONCLUSION. DWI is a sensitive, fast sequence and does not require a contrast agent, which makes it a good and cost-effective alternative for imaging sacroiliac joints. DWI also offers the possibility of quantifying diffusion coefficients of the lesions, which helps to discriminate between normal and involved subchondral bone.
Keywords: ankylosing spondylitis; diffusion-weighted imaging; MRI; sacroiliitis; spondylarthritis; spondyloarthritis